Incidence of Primary Dental Injuries in a Pediatric Emergency Department - Shaker Saleh M Alosman,; Abdullah salehalsamani,; Mahmoud Jawad H. Alawa,; Saleh Salem Saleh Alshehri,; Abdullah salehalsamani,; Jabril Mohammed Yahya Otudi,; Abdulaziz Alharthi,; Afnan Abdulrahman Aldosari, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Traumatic dental injuries (TDIs) are a significant public health concern for children, as they can lead to functional, aesthetic, and emotional consequences. These injuries are commonly observed in young children due to their developing motor skills and high activity levels. While TDIs affect both primary and permanent teeth, there is limited research focusing specifically on primary dental injuries. The importance of early intervention in these cases is emphasized, as untreated trauma to primary teeth can affect the development of permanent teeth. This study aims to investigate the prevalence, causes, and outcomes of primary dental injuries in pediatric patients presenting to the emergency department (ED). Methods: A retrospective study was conducted at [Location] Children's Hospital, where 541 pediatric patients with dental trauma were treated in the ED over a defined time period. The study included children aged 18 years or younger, and data were collected from their emergency dental consultations, including patient demographics, injury causes, treatment outcomes, and follow-up care. Descriptive statistics and χ² tests were used for data analysis. Ethical approval was obtained from the Human Subjects Research Committee. Results: Among 1,459 pediatric patients treated for dental emergencies, 37% (541 cases) involved dental trauma. The majority of cases were male (59%), and dental trauma peaked during the summer months, especially between 4 PM and 12 PM. Falls were the most common cause of injury (63%), particularly among children under seven. Soft tissue injuries were documented in 91% of cases, with lacerations occurring in 32% of patients, especially in younger children. Hard tissue injuries were primarily fractures (33%) and luxations (18%). Tooth fractures were more common in male patients, particularly in those over 12 years. A significant portion of patients received pulp therapy (19%), and 16% required tooth extractions, particularly in children under seven. Follow-up care was recommended for 61% of patients. Conclusion: TDIs are prevalent in pediatric emergency settings, with falls being the leading cause of injury. Early intervention and accurate management are critical for preventing long-term consequences, particularly concerning the development of permanent teeth. Pediatric emergency departments should be equipped to handle dental trauma, and timely referrals to specialized dental care are essential to ensure optimal outcomes. Future studies should explore the impact of early treatment and preventive strategies to reduce the incidence of dental injuries in young children.